Effectiveness of exercise-based rehabilitation for depressive symptoms, anxiety, and health-related quality of life in adults with rheumatoid arthritis: A systematic review and meta-analysis of randomized controlled trials - Yan Xiao; Jinghui Zhong; Kebao Zhang; Xuesong Yang (PLoS ONE, 2026)
Background Rheumatoid arthritis is frequently accompanied by depressive symptoms, anxiety, and impaired health-related quality of life. Although exercise is recommended as part of comprehensive care, its effects on psychological outcomes and quality of life remain uncertain. This systematic review and meta-analysis evaluated structured exercise interventions for adults with rheumatoid arthritis. Methods PubMed, Embase, CENTRAL, Web of Science, Scopus, PsycINFO, and EBSCOhost were searched from inception to November 26, 2025. Randomized controlled trials comparing structured exercise with non-exercise control conditions were included. Random-effects meta-analyses used Hedges’g standardized mean differences with 95% confidence intervals. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool, and certainty of evidence was rated using GRADE. The protocol was retrospectively registered with INPLASY (INPLASY202610082). Results Fifteen trials involving 1652 participants were included. Compared with non-exercise controls, structured exercise reduced depressive symptoms (11 trials, 685 participants; standardized mean difference, −0.49; 95% confidence interval, −0.70 to −0.28; P < 0.001; I² = 42%; moderate certainty). Low-certainty evidence suggested reductions in anxiety (7 trials, 403 participants; standardized mean difference, −0.45; 95% confidence interval, −0.65 to −0.25; P < 0.001; I² = 0%) and improvements in quality of life or health-related quality of life (7 trials, 564 participants; Hedges’ g standardized mean difference, 0.45; 95% confidence interval, 0.18 to 0.71; P = 0.001; I² = 50%). Subgroup analyses showed no statistically significant difference between conventional exercise and mind-body exercise. Conclusions Structured exercise probably reduces depressive symptoms and may reduce anxiety and improve quality of life in adults with rheumatoid arthritis, supporting its use as an adjunct to comprehensive care. Larger, better-reported trials with longer follow-up are needed to clarify durability, clinical importance, and optimal delivery.